Involvement of the GABAergic system in PTSD and its therapeutic significance - Huang, Junhui; Xu, Fei; Yang, Liping; Tuolihong, Lina; Wang, Xiaoyu; Du, Zibo; Zhang, Yiqi; Yin, Xuanlin; Li, Yingjun; Lu, Kangrong; Wang, Wanshan (Frontiers in Molecular Neuroscience, 2023)
The neurobiological mechanism of post-traumatic stress disorder (PTSD) is poorly understood. The inhibition of GABA neurons, especially in the amygdala, is crucial for the precise regulation of the consolidation, expression, and extinction of fear conditioning. The GABAergic system is involved in the pathophysiological process of PTSD, with several studies demonstrating that the function of the GABAergic system decreases in PTSD patients. This paper reviews the preclinical and clinical studies, neuroimaging techniques, and pharmacological studies of the GABAergic system in PTSD and summarizes the role of the GABAergic system in PTSD. Understanding the role of the GABAergic system in PTSD and searching for new drug targets will be helpful in the treatment of PTSD.